PRICE REGULATION MODEL FOR POSTAL SERVICES (Perner's Contacts, 2013)
The method of price regulation of the domestic postal services within the regulation used in the Czech postal sector is not suitable. A more effective and more transparent method of price regulation of postal services would be the price-cap method which is already used in several EU member states. There is the need to consider the necessary scope of that price regulation, i.e. which concrete postal services should be regulated before the application of this regulation method.